(untitled) (International Journal of Engineering and Computer Science, 2013)
Using the web usage mining effectively as an underlying mechanism for web personalization and recommender system can enable us to achieve efficient web navigation system. Using the user usage patterns as a tool of prior information we can very well keep an intelligent base of most common user choices. Also by using the effective web structuring methods and web usage mining we will have a system that will ensure a completely different web navigation experience. Specifically, the proposed changes to the existing website will improve the user navigation on a website while minimizing alterations to its current structure. The users who are more affected by inefficiency of website are likely to benefit more from the improved structure.